THE IDEAL CONCEPT FOR THE USE OF SUPPORT FUND BY THE UNITED DEVELOPMENT PARTY IN CILEGON CITY BANTEN TOWARDS COMMUNITY POLITICAL EDUCATION - King Faisal Sulaiman; Muzakki, Ardi (Awang Long Law Review, 2025)
This research discusses the implications of the United Development Party (PPP)’s support fund in Cilegon City, Banten, on community political education during the 2016-2021 period. The main objective of this research is to analyze the effectiveness of the use of party support funds in improving people's political understanding, as well as identifying obstacles in its management. The research method used is a qualitative approach with descriptive analysis, which includes literature studies and interviews with relevant parties, such as party administrators and community beneficiaries of political education programs. The results showed that although support funds have been allocated for political education programs, their use still faces various challenges, such as complex disbursement procedures, lack of transparency, and a larger allocation of funds for party operations than for political education programs. In addition, the lack of coordination between the DPC of PPP Cilegon City and the central party is also an obstacle to the effectiveness of the program. Supervision and evaluation of the use of funds are also still limited, thus reducing the impact of political education for the community. This research recommends optimizing the use of support funds by increasing the allocation for political education, increasing transparency and accountability in fund management, and strengthening coordination between the DPC and the central party. In addition, innovations in political education methods, such as the use of digital technology and social media, can increase the reach and effectiveness of the program.